Association between environmental cadmium exposure and increased mortality in the U.S. National Health and Nutrition Examination Survey (1999–2018) - Moon, Shinje; Lee, Junghoon; Yu, Jae Myung; Choi, Hoonsung; Choi, Sohyeon; Park, Jeongim; Choi, Kyungho; Kim, Ejin; Kim, Ho; Kim, Min Joo; Park, Young Joo (Journal of exposure science & environmental epidemiology, 2023)
Background Cadmium (Cd) is toxic to human health and increases overall mortality. In this study, we investigated the association between Cd exposure and all-cause, cardiovascular (CVD), and cancer mortality in the general population and the mediating effect of smoking on these association. Methods We used data from U.S. National Health and Nutrition Examination Survey for 1999–2018. To evaluate the hazard ratio (HR) for mortality, a multiple Cox regression analysis was conducted by adjusting for age, sex, race/ethnicity, body mass index, smoking, alcohol, hypertension, diabetes, hyperlipidemia, and history of CVD and cancer. A causal mediation analysis was performed to estimate the effects of smoking. Results Among the 31,637 subjects, 5452 (12.3%) died. Blood Cd concentrations were significantly associated with all-cause (HR 1.473, 95% confidence interval [CI] 1.403–1.546, p < 0.001), CVD (HR 1.445, 95% CI 1.344–1.554, p < 0.001), and cancer (HR 1.496, 95% CI 1.406–1.592, p < 0.001) mortality. Urinary Cd concentrations were also significantly associated with them. Using feature selection via machine learning, the importance of Cd in all-cause and cancer mortality was second only to age. The association between Cd concentrations and all-cause mortality was significant in both ever-smokers and never-smokers. The mediating effect of smoking was estimated at 32%, whereas a large proportion (68%) remained a direct effect of Cd. In a subgroup analysis of subjects with cancer history, blood Cd concentrations were significantly associated with cancer-related deaths in those with a history of breast, gastrointestinal, and skin cancers. Conclusion High Cd exposure is an important risk factor for all-cause, CVD, and cancer mortality among the general population. Cd exposure increased the risk of death even in never-smokers, and its effects unrelated to smoking were substantial, suggesting the importance of regulating other sources of Cd exposure such as food and water. Impact Statement Using national large-scale data, we found that low-level environmental exposure to cadmium significantly increased the risk of all-cause, cardiovascular, and cancer mortality in the general population even after adjusting for several risk factors. Although smoking is a major source of cadmium exposure, cadmium was nevertheless significantly associated with all-cause mortality in never-smokers, and the mediating effect of smoking on this association was only 32%. Hence, other sources of cadmium exposure such as food and water may be important.